HUBUNGAN PERUBAHAN FISIK DENGAN BODY IMAGE REMAJA PUTRI DI PONDOK PESANTREN DARUL HIKMAH KEDUNGMALING SOOKO MOJOKERTO - Ratnaningsih, Tri; Zakiyah, Nurul (JURNAL KEPERAWATAN SEHAT, 2016)
The concrete change on female adolescents is physical change where the body develops fastly until reaching adults body shape that followed with the development of reproduction capacity. The physical change is closely related with adolescents’ condition. A good condition bumps into a good adolescents’ physical change. The role changing, physics and psychologist influence Body Image of somebody and Body Image has sturdy effect in physical estimation. The objective of this research is to analyze the correlation of physical change with Body Image of female adolescents in Pondok Pesantren Darul Hikmah Kedung Maling Sooko Mojokerto. Population on this research is whole female adolescents in Pondok Pesantren Darul Hikmah Kedung Maling Sooko Mojokerto, and the sample of this research are 34 respondents that taken by using purposive sampling technique. This research is analytic correlation research and using Cross Sectional Approach. The tabulation of data analysis used coding, scoring, tabulating, and tested by using Chi Square. Based on the result of research shows the significant correlation by using Chi Square test α=0.05 get that X2≥ X2tabel (25,972 > 3,81) means there is correlation between physical changing with body image of female adolescents in Pondok Pesantren Darul Hikmah Kedung Maling Sooko Mojokerto. The physical changing will influence on psychology, cognitive and social condition. The uncomfortable feeling on the body and misunderstanding on facing physical changing will show new behaviors on adolescents in behaving it.Keywords: Physical Changing, Body Image, Female Adolescents